Blood clearance kinetics and organ delivery of medium-chain triglyceride and fish oil-containing lipid emulsions: Comparing different animal species. Issue 3 (March 2021) - Hu, Chengming; Ding, Huanzhong; Zhuang, Qiulin; Llanos, Pierre; Pillay, Thivashnee; Hernandez, Carlo; Carpentier, Yvon A.; Deckelbaum, Richard J.; Chang, Chuchun L.
Summary: Background & aims: Medium-chain triglycerides (TG) (MCT) and fish oil (FO) TG are incorporated as the core TG component into intravenous (IV) lipid emulsions for infusion in parenteral nutrition. Bolus injections of IV emulsions, on the other hand, have emerged as a novel therapeutic approach to treat various acute disorders. However, intravascular metabolism and organ delivery of acute IV injection of emulsions containing both MCT and FO are not fully defined, nor have they been characterized across common experimental animal models. We characterized and compared blood clearance kinetics and organ distribution of bolus injections of MCT/FO emulsions among different animal species. We also examined whether sex differences or feeding status can affect catabolic properties of MCT/FO lipid emulsions. Design: Blood clearance rates of lipid emulsions with specific TG composition were compared in rats IV injected with [3H]cholesteryl hexadecyl ether labeled pure n-6 long-chain (LCT) and n-3 FO TG lipid emulsions, or emulsions containing MCT and FO at different ratios (wt/wt), which include 8:2 (80% MCT: 20% FO), 5:4:1 (50% MCT: 40% LCT: 10% FO) and SMOF (30% LCT: 30% MCT: 25% olive oil: 10% FO). Dose-response effects (0.016 mg–1.6 mg TG/g body weight) of the MCT/FO 8:2 emulsions on blood clearance properties and organ delivery were determined in both mice and rats. Blood clearance kinetics and organ uptake of MCT/FO 8:2 emulsions were compared between male and female rats and between fed and fasted rats. Changes in plasma lipid profiles after acute injections of MCT/FO 8:2 lipid emulsion at different doses (0.043, 0.133, and 0.4 mg TG/g body weight) were characterized in non-human primates ( Cynomolgus monkeys). Results: MCT/FO 8:2 emulsion was cleared faster in rats when compared with other emulsions with different TG contents. Mice had faster blood clearance and higher fractional catabolic rates (FCR) when compared with the rats injected with MCT/FO 8:2 emulsions regardless of the injected doses. Mice and rats had similar plasma TG and free fatty acid (FFA) levels after low- or high-dose injections of the MCT/FO emulsion. Tissue distribution of the MCT/FO 8:2 lipid emulsion are comparable between mice and rats, where liver had the highest uptake per recovered dose among all organs (>60%). Feeding status and sex differences did not alter the blood clearance rate of the MCT/FO 8:2 emulsion in rats. In a nonhuman primate model, dose-response increases in plasma TG and FFA were observed after IV injection of MCT/FO 8:2 emulsions within the 1st 10 min. Conclusion: A lipid emulsion containing both MCT and FO TG is cleared rapidly in blood and readily available for organ uptake in rodent and primate animal models. Characterization of the blood clearance properties of the MCT/FO 8:2 emulsion administered in various animal models may provide further insight into the safety and efficacy profiles for future therapeutic use of bolus injections of MCT/FO emulsions in humans.